A gender-based study of symptoms and risk factors associated with mortality in COVID-19 patients in a tertiary care hospital, Lahore - Bukhari, Syeda Filzah; Saad Butt; Muhammad Nadeem Yousaf (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the symptoms and risk factors associated with gender-specific mortality among coronavirus disease-2019 patients. Method: The retrospective, descriptive, cross-sectional study was conducted at the coronavirus disease-2019 ward of the Jinnah Hospital, Lahore, Pakistan, and comprised record of confirmed cases of coronavirus disease-2019 diagnosed on the basis of characteristic clinical symptoms, radiological findings and polymerase chain reaction positivity from May 1 to August 31, 2020. Clinical symptoms, comorbidities and outcomes were extracted from the medical records. Data was analysed using SPSS 23. Results: Of 337 cases, 132(39.2%) died. Among the deceased, 84(64%) were males with median age 61.5 (interquartile range: 22) and 48(36%) were females with median age 54.5 (interquartile range: 25).There were more female non-survivors who suffered from kidney disease 10(66.7%) than male non-survivors 5(33.3%) (p<0.05). Ischemic heart disease was more common among males than females (p=1.62). Conclusion: The mortality rate in males was higher compared to females. The symptoms and risk factors associated with mortality varied between the genders. Key Words: Mortality, Gender, Risk factors.